Finland’s Network Media Economy : Growth, Concentration and Upheaval, 2018-2023 - Grönlund, Mikko (Canada, 2026)
This report presents the preliminary findings on Finland as part of the Global Media and Internet Concentration Project (GMICP), an international research initiative funded by the Canadian Social Science and Humanities Research Council. Covering the years 2018 to 2023, the report provides a comprehensive overview of market and concentration trends in Finland’s media and internet sectors. The GMICP investigates global developments in media and internet markets, and this report contributes to that effort by examining key Finnish segments in a way that allows for international comparison.
The scope of the report is broad, encompassing traditional media, digital content production, communication infrastructure, and new areas shaped by the convergence of IT, telecommunications, and media. It focuses on selected segments that reflect wider global trends, offering insights into how these markets have evolved and become increasingly concentrated. Although Finland's media and communications industry is not among the largest in economic terms, it plays a crucial societal role by enabling interpersonal communication, supporting democratic discourse, and shaping the national information environment. Understanding ownership structures, concentration levels, and international influence is thus essential for both researchers and policymakers.
Between 2018 and 2023, the total estimated revenues of Finland's networked media economy grew steadily, rising from EUR 10.6 billion in 2018 to EUR 12.05 billion (around USD 13 billion) in 2023. This overall increase of approximately 14% reflects growth across several key sectors, despite some fluctuations along the way. This estimate of EUR 12 billion is a conservative figure due to data gaps, especially in core internet sectors such as those dominated by global tech giants like Google and Facebook, and infrastructure services like content delivery networks (CDNs). Traditional and online media services, the largest segment of Finland’s networked media economy, experienced moderate fluctuations, peaking at EUR 6.8 billion in 2021 and settling at EUR 6.6 billion in 2023. Although smaller in scale, online advertising grew the fastest, increasing by 67% from EUR 421 million in 2018 to EUR 704 million in 2023, highlighting a clear shift in advertising spending toward digital platforms. Telecom and internet access services remained stable, generating approximately EUR 3.2 billion in 2023. Meanwhile, the data centre sector demonstrated steady and robust growth, expanding by over 40% from EUR 1.1 billion in 2019 to EUR 1.5 billion in 2023. This growth has been concentrated in access and backbone infrastructure, while legacy media sectors, such as newspapers and magazines, continue to decline. These developments reflect the increasing dominance of powerful, largely US-based digital actors in shaping Finland’s media and communications environment, raising broader concerns for national media policy and European regulatory frameworks.
In 2024, telecommunications company Elisa Oyj was the largest player in Finland’s networked media economy by turnover, generating EUR 2.2 billion. It was followed closely by game company Supercell, with a turnover of EUR 1.7 billion. Telia Finland Oyj and Sanoma Oyj, the latter being Finland’s leading cross-media company, each reported turnover of approximately EUR 1.4 billion. The third major telecom operator, DNA, completed the top five with EUR 1.1 billion in turnover. Public service media Yleisradio Oy reported a turnover of EUR 527 million.
The findings highlight that Finland’s media and communications sectors are generally highly concentrated. In most sub-sectors, a small number of firms dominate, a dynamic partly explained by Finland’s relatively small population of 5.6 million. Core internet applications, particularly search engines, exhibit extreme concentration, often approaching monopolistic conditions, with significant control held by US companies. Traditional wired telephony has become obsolete, and wireless services now represent the largest share of telecom revenues. At the same time, established entertainment media, such as radio, books, and at least to some extent also television, remain relatively stable, maintaining consistent revenue streams despite digital disruption. The Finnish digital games industry stands out as a globally competitive and export-oriented sector, contributing significantly to the national economy. Conversely, the newspaper industry continues to struggle, with declining print circulation and limited digital revenue growth failing to compensate for losses in advertising and subscriptions.
Between 2018 and 2023, the CR4 scores for traditional and online media reveal significant concentration trends and market dynamics. Commercial TV broadcasting remained highly concentrated, increasing slightly from 92.7 to 94.7. In contrast, online video services saw a notable decline in concentration, from 72.5 in 2020 to 60.7 by 2022, suggesting rising competition. Digital games also experienced a steady drop, from 91.1 in 2018 to 73.1 in 2023, reflecting market diversification. The book sector showed the opposite trend, increasing its CR4 score from 44.9 to 66.4, indicating growing consolidation. Overall, traditional telecom and broadcasting sectors remain tightly concentrated, while digital and online segments show more competitive and shifting market dynamics.
From 2018 to 2023, HHI scores for the telecoms and internet access sectors indicate sustained high concentration levels, particularly in wireless services. Internet service providers and wireline services also showed high concentration. Notably, commercial TV broadcasting saw a steady rise in HHI, reaching 3,227 by 2023, reflecting growing market dominance by top firms. In contrast, online video services had much lower HHI scores (around 1,563 in 2022–2023), pointing to a more competitive and fragmented market. Film exhibition and digital games sectors remained highly concentrated, despite some fluctuations. Overall, traditional media and telecom sectors remain tightly controlled by a few large players, while newer and digital markets show signs of greater competitiveness
The report relies on publicly available and mostly free statistics. Whenever possible, it draws on official statistical sources and annual company reports; however, in many instances, it has had to use a variety of other sources, including ministerial reports, trade association data, consultancy reports, and other unofficial sources. A major challenge identified in the report is the lack of comprehensive and reliable statistical data, particularly for emerging internet services and content markets. While telecommunications data are relatively robust, statistics on digital platforms, revenue flows, and market shares are fragmented or altogether missing. This data gap hinders research, policymaking, and regulation. Recent studies (e.g., Ala-Fossi et al., 2018 and 2020; Lehtisaari et al., 2024) have highlighted growing concerns about the increasing difficulty in tracking the media sector's development, with some aspects becoming nearly impossible to monitor due to the narrowing of available data.
The most recent setback in data collection occurred at the end of 2024, when Statistics Finland decided to discontinue its mass media statistics in line with government austerity measures. This loss represents a serious setback for understanding the Finnish media landscape, as the dataset had been a vital resource for nearly three decades. Given these challenges, the report strongly recommends strengthening the collection and availability of official statistics in the media and communications sector—an increasingly urgent need in light of forthcoming EU legislation such as the European Media Freedom Act.
In conclusion, the report underscores both the structural shifts occurring in Finland’s media and communications sectors and the pressing need for better data to understand and manage them. Concentration remains a defining feature across most markets, driven by global tech dominance and local market dynamics. Ensuring transparency, competitiveness, and democratic accountability in this environment will depend on robust data and informed policy responses.